Walter de la Mare : critical appraisals - Kajita, Yui; Leighton, Angela; Nickerson, A. J. ([Liverpool] : Liverpool University Press, 2022)
This book aims to put Walter de la Mare back on the literary map. A writer beloved by many, he has nevertheless remained on the sidelines of literary history. Walter de la Mare: Critical Appraisals promises to restore his reputation as one of the most memorably haunting of poets, as well as a peculiarly unnerving writer of ghost stories. A collection of varied, wide-ranging essays on de la Mare's poetry, stories, novels, reviews and lectures, it puts his work beside that of many of his famous contemporaries, including Thomas Hardy, Robert Frost, W. H. Auden, T. S. Eliot and Katherine Mansfield. It also contains an invaluable survey of his archive, much of it unpublished, and a number of newly commissioned poems reflecting on his legacy. This multifaceted volume will be of interest to students working on twentieth-century poetry, the short story, the nature and limits of modernism and British intellectual history, as well as on de la Mare himself.List of contributors: Catherine Charlwood, Guy Cuthbertson, Peter Davidson, Giles de la Mare, Andrew Doyle, Suzannah V. Evans, Adam Guy, Robin Holloway, Yui Kajita, Zaffar Kunial, Gregory Leadbetter, Angela Leighton, Erica McAlpine, Jenny McDonnell, Will May, Andrew Motion, Paul Muldoon, A. J. Nickerson, Seamus Perry, Adrian Poole, Camille Ralphs, Vidyan Ravinthiran, Peter Scupham, A. E. Stallings, Mark Valentine, Rory Waterman, Anne Welsh, David Wheatley, Rowan Williams, William Wootten.
Includes bibliographical references and index
JSTOR
Keywords: De la Mare, Walter, -- 1873-1956 -- Criticism and interpretation; De la Mare, Walter, -- 1873-1956; Criticism, interpretation, etc